Characteristics of Visual Evoked Potential in Different Parts of Visual Impairment - Dai, Ding-Kun; Yang, Li; Meng, Huan-Huan; Chen, Xi-Ping; Tao, Lu-Yang (Fa yi xue za zhi, 2021)
To study the quantitative and qualitative differences of visual evoked potential (VEP) in monocular visual impairment after different parts of visual pathway injury. A total of 91 subjects with monocular visual impairment caused by trauma were selected and divided into intraocular refractive media-injury group (eyeball injury group for short), optic nerve injury group, central nervous system injury and intracranial combined injury group according to the injury cause and anatomical segment. Pattern Reversal visual evoked potential (PR-VEP) P100 peak time and amplitude, Flash visual evoked potential (F-VEP) P2 peak time and amplitude were recorded respectively. SPSS 26.0 software was used to analyze the differences of quantitative (peak time and amplitude) and qualitative indexes (spatial frequency sweep-VEP acuity threshold, and abnormal waveform category and frequency) of the four groups. Compared with healthy eyes, the PR-VEP P100 waveforms of the intraocular eyeball injury group and the F-VEP P2 waveforms of the optic nerve group showed significant differences in prolonged peak time and decreased amplitude in injured eyes ( <0.05). The PR-VEP amplitudes of healthy eyes were lower than those of injured eyes at multiple spatial frequencies in central nervous system injury group and intracranial combined injury group ( <0.05).The amplitude of PR-VEP in patients with visual impairment involving central injury was lower than that in patients with eye injury at multiple spatial frequencies. The frequency of VEP P waveforms reaching the threshold of the intraocular injury group and the optic nerve injury group were siginificantly different from the intracranial combined injury group, respectively( <0.008 3), and the frequency of abnormal reduction of VEP amplitude of threshold were significantly different from the central nervous system injury group, respectively( <0.008 3). VEP can distinguish central injury from peripheral injury, eyeball injury from nerve injury in peripheral injury, but cannot distinguish simple intracranial injury from complex injury, which provides basic data and basis for further research on the location of visual impairment injury.